Exploring the Retinal Binding Cavity of Archaerhodopsin-3 by Replacing the Retinal Chromophore With a Dimethyl Phenylated Derivative - Tsuneishi, Taichi; Takahashi, Masataka; Tsujimura, Masaki; Kojima, Keiichi; Ishikita, Hiroshi; Takeuchi, Yasuo; Sudo, Yuki (Frontiers in Molecular Biosciences, 2021)
Rhodopsins act as photoreceptors with their chromophore retinal (vitamin-A aldehyde) and they regulate light-dependent biological functions. Archaerhodopsin-3 (AR3) is an outward proton pump that has been widely utilized as a tool for optogenetics, a method for controlling cellular activity by light. To characterize the retinal binding cavity of AR3, we synthesized a dimethyl phenylated retinal derivative, (2E,4E,6E,8E)-9-(2,6-Dimethylphenyl)-3,7-dimethylnona-2,4,6,8-tetraenal (DMP-retinal). QM/MM calculations suggested that DMP-retinal can be incorporated into the opsin of AR3 (archaeopsin-3, AO3). Thus, we introduced DMP-retinal into AO3 to obtain the non-natural holoprotein (AO3-DMP) and compared some molecular properties with those of AO3 with the natural A1-retinal (AO3-A1) or AR3. Light-induced pH change measurements revealed that AO3-DMP maintained slow outward proton pumping. Noteworthy, AO3-DMP had several significant changes in its molecular properties compared with AO3-A1 as follows; (i) spectroscopic measurements revealed that the absorption maximum was shifted from 556 nm to 508 nm and QM/MM calculations showed that the blue-shift was due to the significant increase in the HOMO-LUMO energy gap of the chromophore with the contribution of some residues around the chromophore, (ii) time-resolved spectroscopic measurements revealed the photocycling rate was significantly decreased, and (iii) kinetical spectroscopic measurements revealed the sensitivity of the chromophore binding Schiff base to attack by hydroxylamine was significantly increased. The QM/MM calculations show that a cavity space is present at the aromatic ring moiety in the AO3-DMP structure whereas it is absent at the corresponding β-ionone ring moiety in the AO3-A1 structure. We discuss these alterations of the difference in interaction between the natural A1-retinal and the DMP-retinal with binding cavity residues.